The Scientific Research on motivation for learning as an important element of social and economic sciences in the context of sphere of security and defense - PETROVA, Elitsa (Journal of Economic Development, Environment and People, 2020)
This article gives a brief overview of a study conducted on motivation for learning as an important element of social and economic sciences in the context of the sphere of security and defense. The research is an important scientific work of the author and was developed in the period 2012-2018. At present, its results have been approved, considered appropriate and acceptable, and are applied at the National Military University in Bulgaria.